Helmintofauna de Euthynnus lineatus (Perciformes: Scombridae) en Jalisco, México - Castillo-Sánchez, E (Universidad de Costa Rica, 1997)
The helmintbological record of Euthynnus lineatus consists of eigtb species. trematodes are the better represented group witb five species. Feeding habits is the Cactor that determine the presence of a wide variety of helmintb parasites in tbis host species.